Analysis of the referral pattern and wait time for hip arthroscopy in a single payer publicly funded health care system. Issue 1 (29th May 2019) - Petrera, Massimo; Yanez‐Siller, Federico; Whelan, Daniel; Hoit, Graeme; Mahjoob, Maryam; Chahal, Jas; Dwyer, Tim
Abstract: Rationale and objectives: To analyse the referral pattern for hip pain and to investigate the wait time for an orthopaedic assessment by a hip arthroscopy surgeon in a single payer health care system. We hypothesized that a significant delay from time of onset of symptoms to time of assessment by a hip arthroscopy surgeon exists. Method: Retrospective review of prospectively collected data in an academic hospital in a single payer health care system. An electronic database analysis was conducted searching for all referrals for hip pain between February 2017 and June 2017. Data were then analysed with the aim to identify the most common reason for hip referral, calculate the duration of symptoms between onset and orthopaedic assessment, and categorize previous investigations and treatments. Results: A total of 96 patients were included (47 male and 49 female). Main source of referrals was Family Medicine Physicians in 37% of cases and Primary Care Sports Medicine Physicians in 35%. The most common reason for referral was labral tear in 44.7% of cases followed by combined femoroacetabular impingement and labral tear in 21.8%. The duration of symptoms was longer than 2 years in 42% of cases and between 1 and 2 years in 40% of cases. Twenty percent of patients had previous intra‐articular injection while 53% of patients had physiotherapy treatment (64% of patient underwent physiotherapy for longer than 6 months). Conclusion: In the Canadian single payer health care system, a significant delay from the time of onset of symptoms to the time of assessment by a hip arthroscopy surgeon exists with the vast majority of patients in our cohort waiting more than 1 year. It is unknown if this delay affects the patient outcomes. This will require further investigation. Certainly, based on our findings, we should advocate for a better screening process, centralized referrals to hip arthroscopy specialists, and appropriate patient work‐up.